(untitled) (Research, Society and Development, 2020)
The need for new technologies and efficient management of resources requires the use of performance indicators whose information ensures management in a visual and fast way. Today, maintenance is a sector that is technological and developed, and indicators that can develop the team a lot. The proposed study aims to analyze the individual performance indicators of the maintenance team, in addition to identifying the main problems affecting efficiency in the sector. To this end, a case study was carried out in the maintenance sector of a food industry. With the subsequent application of Pareto, it was possible to observe which the most impacting points were. After the application of Ishikawa, it is possible to identify the causes, and with the 5W2H points of improvement in the process were defined, planning with the actions for monitoring and execution, this action plan was proposed because of all analysis of the indicators. It is concluded that the indicators are necessary for a good management, and the application of the tools facilitates the vision of the indicators and still allows the improvement of them.